PENGEMBANGAN MEDIA POP-UP BOOK PADA MATA PELAJARAN IPA MATERI SIKLUS HIDUP HEWAN KELAS III - Aisyah, Siti; Erwin Rahayu Saputra; Agnestasia Ramadhani Putri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study focuses on the development of a learning media in the form of a pop-up book for the science subject, aimed at third-grade elementary school students, specifically on the topic of the animal life cycle. The background of this research is the low understanding and motivation of students in learning the animal life cycle material due to the use of unengaging learning tools that lack active student involvement. The method used in this study is Research and Development (R&D) with the ADDIE development model, which includes five stages: Analyze, Design, Develop, Implement, and Evaluate. The developed media is a three-dimensional pop-up book designed to be attractive and interactive, featuring illustrations of the life cycles of several animals such as butterflies, frogs, mosquitoes, cockroaches, grasshoppers, and dragonflies. Validation results from experts indicate that the media is highly feasible for use, with assessment percentages of 93.3% from media experts, 92% from content experts, 80% from instructional design experts, and 90.9% from teachers as users. A limited trial involving 19 students showed a very practical response with percentages of 92.3% from students and 97.5% from teachers. A wider trial involving 20 students showed a student response of 94% while the teachers’ response remained at 97.5%. Based on these results, the pop-up book media is considered feasible and practical to implement in elementary school science learning activities, and it is capable of enhancing students’ understanding and interest in learning abstract topics such as the animal life cycle.